Consumer Purchase Decision towards Private Label Brands: Evidence from the Indian Market - Ajay Singh; Rahul Gupta; Amol Kumar (International Journal of Supply Chain Management, 2018)
The aim of this study is to explore the key factors which Indian consumers considers during purchase of Private label brand products and how these identified factors impact the purchase decision of consumers towards private label brand. The research is initially exploratory in nature followed by causal research to test various hypothesis developed. The research instrument used is structured questionnaire to collect responses from different consumers in retail segment of National Capital Region (NCR) in India. Thereafter factor analysis followed by multiple regression analysis was performed. EFA explored five key factors price consciousness, quality variability, brand image, store image and self perception. Thereafter hypothesis testing was done on explored factors to study the impact on PLB purchase decision which revealed that Brand Image is a most significant factor followed by Price consciousness, Quality Variability, Store Image whereas self perception emerged as insignificant as it varies among different consumers. Keywords- Private Label Brands, Store brands, Exploratory Factor Analysis, Purchase Decision, Multiple Regression Analysis.